1998 Financial review: BRAC RDP/RCP programme - Kelley, Brian; Pikholz, Lynn (Shorebank Advisory Services, 2016)
1. Opening reflections 2. Impact of the flood and funding requirements 3. Portfolio risk management and credit related activities 4. Management and analysis of saving activities 5. Branch and RDP financial sustainability 6. Notes on the challenge of growth 7. Other areas of special donor concern